2014
DOI: 10.3233/ip-140328
|View full text |Cite
|
Sign up to set email alerts
|

Big data, open government and e-government: Issues, policies and recommendations

Abstract: The transformative promises and potential of Big and Open Data are substantial for e-government services, openness and transparency, governments, and the interaction between governments, citizens, and the business sector. From "smart" government to transformational government, Big and Open Data can foster collaboration; create real-time solutions to challenges in agriculture, health, transportation, and more; promote greater openness; and usher in a new era of policy-and decision-making. There are, however, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
155
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(166 citation statements)
references
References 12 publications
1
155
0
10
Order By: Relevance
“…On the other hand, other researchers concluded that distributing e-government content on many channels and social media application was considered a challenge for some users (Bridges, Appel, & Grossklags, 2012). Another important requirement for successful collaboration is the accessibility of big and open data technologies (Bertot et al, 2014). The authors listed several policy instruments for such purpose.…”
Section: Empoweringmentioning
confidence: 98%
See 3 more Smart Citations
“…On the other hand, other researchers concluded that distributing e-government content on many channels and social media application was considered a challenge for some users (Bridges, Appel, & Grossklags, 2012). Another important requirement for successful collaboration is the accessibility of big and open data technologies (Bertot et al, 2014). The authors listed several policy instruments for such purpose.…”
Section: Empoweringmentioning
confidence: 98%
“…Still many researchers realized the direct benefits of open government and open data like: better efficiency, unified processes, crowd sourcing of feedback, better citizens participation, standardized operations, improved operations, and more satisfied citizens (Bertot, Gorham, Jaeger, Sarin, & Choi, 2014;Robinson, Yu, Zeller, & Felten, 2009;Tinati, Carr, Halford, & Pope, 2013).…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Collected as required by law or based on the mission or programmatic areas of government agencies Few characteristics of big data Government has released these data for decades, often on bureau Web sites and in formats that can be read by proprietary statistical software packages; as part of open government, these data are being released in different formats and on centralized platforms as open data Surveillance data (eg, National HIV Surveillance System, New York State Cancer Registry) Collected as required by law or based on mission or programmatic area of government agencies Have characteristics of big data: occur in near real-time (velocity) Government heavily protects these data through various regulations, privacy and confidentiality laws, and patient bill of rights Government has released tabulated health statistics for decades but as part of open government is releasing this information in more interactive and user-friendly formats such as the Centers for Disease Control and Prevention's FluView Interactive and Diabetes Interactive Atlas, and New York's State Prevention Agenda Dashboard Social media data (eg, Twitter, Facebook, FitBit, mobile food diaries) Data are generated personally and distributed socially, often through social networking tools or businesses that compile the data Have characteristics of big data: transactions number in the billions (volume); may include geo tags, text, digital photographs, and videos (variety); and updated in real-time (velocity) As part of open government, public health departments are starting to engage with citizens in nontraditional ways through social media and networking aBig data often exceed personal computing capabilities, need to be stored on larger servers, require strong computational tools, and span a range of data types such as text, numeric, image, video, or combinations thereof 7. …”
mentioning
confidence: 99%